Search
Ask a question
0

Can you tell me on how to simplify this expression: -2(7 - n) + 4

Please show each step to thjs solution. Thank you.

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Armin T. | Tutor in High School or University Biology,Chemistry, and NeuroscienceTutor in High School or University Biolo...
5.0 5.0 (2 lesson ratings) (2)
0
Expression = -2(7-n)+4
 
Step 1: DISTRIBUTE = -2(7) -(-2(n)) + 4=0
Step 2: Multiply it out = -14 +2n + 4=0
Step 3: get a variable (n) on one side. 2n= -4+14 
Step 4: solve = 2n= 10 
Step 5: finish = n=5

Comments

It doesn't say to solve for n.  It says to simplify it.